2017
DOI: 10.1111/echo.13641
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary comparison of two‐dimensional speckle tracking echocardiography and pressure–volume loop analysis in patients with Fontan physiology: The role of ventricular morphology

Abstract: Objective Speckle tracking echocardiography (STE) may be a useful modality for assessing ventricular performance in patients with single ventricle physiology. However, STE’s ability to accurately assess ventricular performance in this population is unknown. The objective of this study was to perform a preliminary comparison of STE measures of myocardial deformation to reference standard measures of function derived from pressure–volume loop (PVL) analysis. Design This was a secondary analysis of a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Averin et al demonstrated that patients with Fontan circulation with borderline end-diastolic pressures at baseline respond to a volume load with evidence of significant diastolic dysfunction (end-diastolic pressures >15 mm Hg) (Figure 3C). Data from speckle tracking echocardiographic imaging have been shown to correlate with results of invasively measured pressure-volume loops, which suggests that accurate tracking of diastolic function might be achieved noninvasively . However, further work is needed to experimentally validate noninvasive methods of computing pressure-volume loops and associated quantitative measures in the single-ventricle population.…”
Section: Assessment Of Diastolic Dysfunctionmentioning
confidence: 99%
“…Averin et al demonstrated that patients with Fontan circulation with borderline end-diastolic pressures at baseline respond to a volume load with evidence of significant diastolic dysfunction (end-diastolic pressures >15 mm Hg) (Figure 3C). Data from speckle tracking echocardiographic imaging have been shown to correlate with results of invasively measured pressure-volume loops, which suggests that accurate tracking of diastolic function might be achieved noninvasively . However, further work is needed to experimentally validate noninvasive methods of computing pressure-volume loops and associated quantitative measures in the single-ventricle population.…”
Section: Assessment Of Diastolic Dysfunctionmentioning
confidence: 99%
“…Nevertheless, there are significant limitations to its use in this population that arise from poor image quality, especially in older patients, and reliance on geometric indices of ventricular size and function, which are not designed for heterogeneous ventricular morphologies [32]. Newer measures of diastolic and systolic performance may be helpful in people with a Fontan circulation [51][52][53][54][55][56][57][58]. Deformation assessment is the most promising, but small studies to date have not shown consistent results or prognostic correlation [52,56,[59][60][61].…”
Section: Echocardiographymentioning
confidence: 99%
“…A growing body of literature has explored single ventricular strain analysis across various ventricular morphologies in the Fontan population. 10,11,26,27 Ventricular global longitudinal strain has been correlated with exercise capacity in other CHD populations 28 and predicts poor outcomes in Fontan populations. 8,29,30 However, only one other study Rato and colleagues studied the relationship between novel speckle tracking derived assessment of global longitudinal strain and peak oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%